The understandings, experiences, and practices of nurses and student nurses concerning domestic violence against women within healthcare encounters in Saudi Arabia: A hermeneutic phenomenological study - Alshammari, Kafi (2021)
Background: Domestic violence and abuse against women (DVA) is a well-established public health issue and a violation of human fundamental rights. DVA is associated with numerous harms with detrimental health consequences on women. In the Saudi Arabian (SA) context, societal and cultural factors inhibit the expression of women’s rights and limit the violence disclosure within marriage and families, further controlling the ability to access or receive appropriate healthcare and support. The experiences and practices of nurses and student nurses concerning care for DVA victims in SA remain unexplored. Therefore, this study aimed to address this gap and also intended to contribute to the nursing educational practice on DVA in SA.